2008
DOI: 10.1073/pnas.0806593105
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient retinal metabolism in cones

Abstract: After bleaching of visual pigment in vertebrate photoreceptors, all-trans retinal is reduced to all-trans retinol by retinol dehydrogenases (RDHs). We investigated this reaction in purified carp rods and cones, and we found that the reducing activity toward alltrans retinal in the outer segment (OS) of cones is >30 times higher than that of rods. The high activity of RDHs was attributed to high content of RDH8 in cones. In the inner segment (IS) in both rods and cones, RDH8L2 and RDH13 were found to be the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 31 publications
(40 reference statements)
2
68
0
Order By: Relevance
“…Cloning of Carp and Mouse RDH Genes-Carp RDH13L (KM377625) and carp RDH14 (KM377626) were cloned from a carp retinal cDNA library (21) based on partial sequences obtained in our previous study (16 WT proteins of carp RDH13L, carp RDH8 (AB439579), carp RDH8L2 (AB439580), and carp RDH13 (AB439581) were expressed in Sf9 cells using Bac-to-Bac Baculovirus Expression System (Invitrogen). Sf9 cells (5 ϫ 10 6 cells) were infected and incubated according to the method described in a manufacturer's protocol.…”
Section: Measurements Of Al-ol Coupling Activity and Nadpmentioning
confidence: 99%
See 2 more Smart Citations
“…Cloning of Carp and Mouse RDH Genes-Carp RDH13L (KM377625) and carp RDH14 (KM377626) were cloned from a carp retinal cDNA library (21) based on partial sequences obtained in our previous study (16 WT proteins of carp RDH13L, carp RDH8 (AB439579), carp RDH8L2 (AB439580), and carp RDH13 (AB439581) were expressed in Sf9 cells using Bac-to-Bac Baculovirus Expression System (Invitrogen). Sf9 cells (5 ϫ 10 6 cells) were infected and incubated according to the method described in a manufacturer's protocol.…”
Section: Measurements Of Al-ol Coupling Activity and Nadpmentioning
confidence: 99%
“…In our previous studies (16,17), we reported that carp cone inner segment membranes show a very efficient 11-cis retinol oxidation activity that does not require the addition of NADP ϩ or NAD ϩ usually required in the oxidation of 11-cis retinol by retinol dehydrogenases (RDHs). Instead, some hydrophobic aldehydes possibly produced in the inner segment supported the reaction: 11-cis retinol was oxidized with concomitant reduction of an aldehyde at a 1:1 molar ratio (aldehyde-alcohol redox-coupling reaction, AL-OL coupling reaction; Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the data from chicken and ground squirrel, the oxidation of 11-cis ROL into 11-cis RAL by RDHs was not effective. The authors speculated that the co-factor might be all-trans RAL rather than NADP+ (Miyazono et al, 2008).…”
Section: Mata Et Al Had Identified Three Novel Catalytic Activities mentioning
confidence: 99%
“…Novel enzymatic activities unique to the intra-retinal visual cycle (in red arrows) include an isomerase (Mata et al, 2005), a RE hydrolase (Bustamante et al, 1995), a retinylester synthase (Mata et al, 2002;Muniz et al, 2006), and a retinol dehydrogenase (Mata et al, 2002;Miyazono et al, 2008). For experimental details see (Schonthaler et al, 2007) and (Fleisch et al, 2008) Figure 4 down.…”
Section: Implication For Therapy Of Retinal Disease (Rod-cone Cone Dmentioning
confidence: 99%